A simple spectrophotometric method for the determination of captopril in pharmaceutical preparations using ammonium molybdate - Ribeiro, Paulo Roberto da Silva; Pezza, Leonardo; Pezza, Helena Redigolo (Eclética Química, 2010)
A simple, rapid and sensitive spectrophotometric method for the determination of captopril (CPT) in pharmaceutical formulations is proposed. This method is based on the reduction reaction of ammonium molybdate, in the presence of sulphuric acid, for the group thiol of CPT, producing a green compound (λmax 407 nm). Beer’s law is obeyed in a concentration range of 4.60 x 10-4 – 1.84 x 10-3 mol l-1 of CPT with an excellent correlation coefficient (r = 0.9995). The limit of detection and limit of quantification were 7.31 x 10-6 e 2.43 x 10-5 mol l-1 of CPT, respectively. The proposed method was successfully applied to the determination of CPT in commercial brands of pharmaceuticals. No interferences were observed from the common excipients in the formulations. The results obtained by the proposed method were favorably compared with those given by the official reported method at 95 % confidence level.